Asian J Biomed Pharmaceut Sci 2019
DOI: 10.35841/2249-622x.66.18-1172
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to evaluate alternative approaches for treatment of urinary tract infections in dogs.

Abstract: Bacteria represent the most common cause of urinary tract infection. Antimicrobial drugs are the cornerstone of treatment of urinary bacterial infections. Because of the chronic nature of urinary bacterial infections urinary tract infection (UTI) and the potential for antibiotic resistance, a natural approach to prevention and treatment is desirable. This study evaluated the efficacy of a polyphenolic extract obtained from cranberries. The product was daily orally administered to 10 dogs with bacterial cystiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In comparison, Cornus mas L. and Sorbus aucuparia L. extracts reported a greater antimicrobial activity against Enterococcus spp. Moreover, recent studies have focused on the in vivo impact of cranberry extract, which has been proven to possess antibacterial qualities that might assist in preventing or minimizing the onset of UTIs in canine patients [ 72 , 73 ]. Additionally, Boerhaavia diffusa L., another intriguing herbal medication, showed evidence of in vivo antimicrobial activity in treating bacterial cystitis in senior dogs, the urine culture being negative on the fifteenth day of treatment [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, Cornus mas L. and Sorbus aucuparia L. extracts reported a greater antimicrobial activity against Enterococcus spp. Moreover, recent studies have focused on the in vivo impact of cranberry extract, which has been proven to possess antibacterial qualities that might assist in preventing or minimizing the onset of UTIs in canine patients [ 72 , 73 ]. Additionally, Boerhaavia diffusa L., another intriguing herbal medication, showed evidence of in vivo antimicrobial activity in treating bacterial cystitis in senior dogs, the urine culture being negative on the fifteenth day of treatment [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, the authors observed no difference between the administration of cranberry or placebos on the presence of anti-adherence activity in a haemagglutination test in the urine of dogs. Another recent study showed a decrease in protein, epithelial cells, leukocytes, and bacterial counts in the urine of 10 dogs with bacterial cystitis 60 days after the start of oral cranberry administration ( 1 ). Unfortunately, the sex of the recruited dogs was not documented and the study did not include a control group of untreated dogs.…”
Section: Discussionmentioning
confidence: 99%
“…The ascending colonisation of the urinary tract by UPEC strains linked to their pili-mediated adhesion to urinary epithelial cells plays a central role in bacterial persistence and the development of UTIs ( 20 , 25 ). Two major adhesion factors play an essential role in UTIs: type 1 fimbriae which have D-mannose derivatives as receptors and pyelonephritis-associated pili, also called P pili, which bind to Gal( 1 , 2 , 3 , 4 )-Gal oligosaccharide receptors ( 23 ). Numerous studies have shown the efficacy of cranberry extracts used in experiments in vitro and ex vivo in reducing the adhesion of UPEC strains to human urinary epithelial cells ( 8 ).…”
Section: Introductionmentioning
confidence: 99%